(untitled) (Journal of Nonlinear Modeling and Analysis, 2026)
This paper considers the existence of global attractors for BBM equation with fading memory. Using some new estimate technique to prove the existence of global attractors in topological space H_1 × L^2_μ(R^+;H_1).